Gaya Komunikasi Pimpinan Dalam Memotivasi Kerja Di Kabupaten Kabupaten Kaur Di Jabodetabek - Sumyati, Sumyati (Universitas Al Azhar Indonesia, 2023)
Leaders' communication style in motivating the work of members in social organizations is important because it is a method used by leaders in expressing their authority and is implemented and communicated to organize and carry out the management of the organization they lead. Managing organizations that are social in nature is not easy because the members they lead are also social, in contrast to organizations such as governments or companies that have a fixed salary so that the application of rules and policies is easier. In social organizations, communication is one of the influences on the smooth running of the organization. The purpose of this study was to determine the style of organizational communication carried out by the leaders of the Bengkulu Citizens Association, Jabodetabek, in motivating the work of organizational members (especially administrators) so that the organization continues to exist and develop, and to find out the factors that make it successful and which hinder it in running the organization. The method used in this research is a descriptive method with a qualitative approach. Primary data collection used interviews with key informants, namely the chief executive of the Jabodetabek PWK and several members (administrators) as supporting informants. Secondary data is collected by way of observation and documentation. Data analysis uses the analytical model proposed by Miles and Huberman, namely the interactive model, where the steps taken are: data reduction; presentation of data; drawing of conclusions; and data verification. Testing the validity of the data using source triangulation and technique triangulation The results showed that the communication style used by the PWK Jabodetabek leadership organization was the equalitarian style, marked by the existence of a two-way flow of message distribution and leaders' concern for and ability to establish good relationships with subordinates in personal matters and in other spheres.